APPROACHES TO STANDARDIZATION OF THE FLOW CYTOMETRY METHOD FOR CELLS IMMUNOPHENOTIPING. CYTOMETRS ADJUSTMENT AND PREPARATION OF PROTOCOLS FOR ANALYSIS - S. V. Khaidukov (Медицинская иммунология, 2014)
Abstract. Immunophenotyping by using a flow cytometry method allows characterizing cells with the help monoclonal antibodies or any other probes and enables to judge their type and a functional condition on presence of this or that set of cellular markers and processes occurring in them. However as a result of carrying out cytometryc analysis could be a number of mistakes at different stages of preparation cytometer to work and that leads to not correct result. To avoid it, the algorithm of preparation of reports for the analysis of cells of peripheral blood is offered. This algorithm of adjustment of the working report looks as follows: check of cytometers work; adjustment of the discriminator; adjustment of sensitivity of channels of light scatters; sensitivity adjustment of channels of fluorescence; introduction of factors of indemnification. Standard adjustments flow cytometers and reports will allow carrying out more correctly the analysis as in clinical diagnostic, and the research purposes.